Freshwater megafauna diversity: Patterns, status and threats. Issue 10 (8th June 2018) - He, Fengzhi; Bremerich, Vanessa; Zarfl, Christiane; Geldmann, Jonas; Langhans, Simone D.; David, Jonathan N. W.; Darwall, William; Tockner, Klement; Jähnig, Sonja C.
Abstract: Aim: Freshwater megafauna remain underrepresented in research and conservation, despite a disproportionately high risk of extinction due to multiple human threats. Therefore, our aims are threefold; (i) identify global patterns of freshwater megafauna richness and endemism, (ii) assess the conservation status of freshwater megafauna and (iii) demonstrate spatial and temporal patterns of human pressure throughout their distribution ranges. Location: Global. Methods: We identified 207 extant freshwater megafauna species, based on a 30 kg weight threshold, and mapped their distributions using HydroBASINS subcatchments (level 8). Information on conservation status and population trends for each species was extracted from the IUCN Red List website. We investigated human impacts on freshwater megafauna in space and time by examining spatial congruence between their distributions and human pressures, described by the Incident Biodiversity Threat Index and Temporal Human Pressure Index. Results: Freshwater megafauna occur in 76% of the world's main river basins (level 3 HydroBASINS), with species richness peaking in the Amazon, Congo, Orinoco, Mekong and Ganges‐Brahmaputra basins. Freshwater megafauna are more threatened than their smaller counterparts within the specific taxonomic groups (i.e., fishes, mammals, reptiles and amphibians). Out of the 93 freshwater megafauna species with known population trends, 71% are in decline. Meanwhile, IUCN Red List assessments reported insufficient or outdated data for 43% of all freshwater megafauna species. Since the early 1990s, human pressure has increased throughout 63% of their distribution ranges, with particularly intense impacts occurring in the Mekong and Ganges‐Brahmaputra basins. Main conclusions: Freshwater megafauna species are threatened globally, with intense and increasing human pressures occurring in many of their biodiversity hotspots. We call for research and conservation actions for freshwater megafauna, as they are highly sensitive to present and future pressures including a massive boom in hydropower dam construction in their biodiversity hotspots.